Outcome from Acute Repsiratory Distress Syndrome: Is It Really Improving? - Jesús Villar; Arthur S Slutsky (Canadian Respiratory Journal)
Assessing the severity of the acute respiratory distress syndrome (ARDS) is important in determining the prognosis in any given patient and in assessing the adequacy of various forms of therapy. Mortality from ARDS has been high since the syndrome was first described almost 30 years ago. Sepsis and extrapulmonary organ failure are the major contributing factors affecting the probability of survival in patients with ARDS. Although studies of ARDS frequently are not comparable because of varying definitions and inhomogeneity of patients, it appears that the mortality rate from ARDS has dropped by about 20% in the past 10 years.